Microfoundations - Maarten C.W. Janssen (Tinbergen Institute, 2006)
This paper gives an overview and evaluates the literature on Microfoundations.
Keywords: B22; D40; E00; 330; Representative Agents; New Keynesian Economics; and New Classical Economics